Banking on Web 2.0 Approaches to Build a Sustainable Enterprise - Rodica M. CÂNDEA; Dan CÂNDEA (Revista de Management Comparat International)
This paper approaches the issue of sustainability in business in a less traditional manner by considering more than just the competitive advantage a company has to build in the rivalry with its competitors. Building enterprise sustainability requires a broader understanding of the interdependencies between the company and its human and natural environments. Effective stakeholder engagement is key and online openness and cooperation bring about new conditions for corporate social responsibility.